2012
DOI: 10.1007/s12031-012-9717-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Newly Identified Gene CAC1 in the Hippocampus of Alzheimer’s Disease Patients

Abstract: Alzheimer's disease (AD), the most common form of senile dementia, is associated with neurodegeneration. The development of Alzheimer's disease is related to abnormalities of cell cycle regulation. Preliminary work showed that a novel gene, CAC1, was highly expressed in tumors and had an oncogene-like function related to cell cycle regulation. The pathogenesis of AD is still incompletely understood. In this study, we measured the expression level of CAC1 in the hippocampus of AD patients to explore the involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…CACULI, also named CAC1, interacts with the CDK2 protein and governs the activity of CDK2, further regulating the cell cycle. The imbalanced expression of CACULI may lead to cell cycle disorder (Kong et al ). Previous studies have shown that abnormal cell cycle regulation promotes the development of Alzheimer's disease and leads to apoptosis by regulating p53 protein activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CACULI, also named CAC1, interacts with the CDK2 protein and governs the activity of CDK2, further regulating the cell cycle. The imbalanced expression of CACULI may lead to cell cycle disorder (Kong et al ). Previous studies have shown that abnormal cell cycle regulation promotes the development of Alzheimer's disease and leads to apoptosis by regulating p53 protein activation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that abnormal cell cycle regulation promotes the development of Alzheimer's disease and leads to apoptosis by regulating p53 protein activation. Moreover, downregulation of CACUL1 levels activates the p53 signaling pathway (Kong et al ; Fukuda et al ). The activation of the p53 protein, which is an important regulator of apoptosis, has been shown to be involved in promoting the expression of pro‐apoptotic members of the BCL‐2 family (Fukuda et al ; Sharma et al ).…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampus, which is an important component of the limbic system, plays a vital role in cognitive processes such as learning, memory consolidation, and information retrieval (Hami et al 2014;Huang et al 2015;Kong et al 2012;Zhao et al 2014). Hippocampal-dependent cognitive function is well known to be influenced largely by the hippocampal cholinergic system (Gold 2003;Hasselmo 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that CACUL1 is involved in ERα and RARα regulation by binding to and repressing their transcription activity in cells 36 37 . Moreover CACUL1 has been reported to be down regulated in hippocampus of Alzheimer disease patients, and up-regulated by H 2 O 2 and Aβ in SHSY-5Y cells 38 . It was also shown that CACUL1 knock-down leads to increase in oxidative stress, suggesting a role in cellular stress responses 38 .…”
mentioning
confidence: 99%
“…Moreover CACUL1 has been reported to be down regulated in hippocampus of Alzheimer disease patients, and up-regulated by H 2 O 2 and Aβ in SHSY-5Y cells 38 . It was also shown that CACUL1 knock-down leads to increase in oxidative stress, suggesting a role in cellular stress responses 38 . However, its biochemical function and biological relevance in stress response mechanisms is not fully understood.…”
mentioning
confidence: 99%